Dried Volumetric Microsampling Approaches for the Therapeutic Drug Monitoring of Psychiatric Patients Undergoing Clozapine Treatment - Marasca, Camilla; Mandrioli, Roberto; Sardella, Roccaldo; Vovk, Tomaž; Armirotti, Andrea; Cavalli, Andrea; Serretti, Alessandro; Protti, Michele; Mercolini, Laura (Frontiers in Psychiatry, 2022)
Clozapine is one of the most widely used second generation antipsychotic drugs (APDs) for the treatment of schizophrenia. Despite the advantages over first-generation drugs, clozapine still shows significant side effects and interindividual variations in efficacy. In order to ensure a frequent therapeutic drug monitoring (TDM) and improve the compliance of psychiatric patients undergoing clozapine treatment, two novel dried microsampling approaches based on whole blood and plasma volumetric absorptive microsampling (b-VAMS and p-VAMS) and microfluidic generated-dried blood spot technology (mfDBS) were developed. The proposed miniaturised strategies by means of VAMS and microfluidic channel-based devices provide several advantages in terms of collection, storage and handling compared to classical blood and plasma processing. Satisfactory validation results were obtained for all microsampling platforms, with mean extraction yields > 85.1%, precision RSD < 5.1%, and stability < 4.5% analyte loss after 30 days for p-VAMS; mean extraction yields > 83.4%, precision RSD < 5.4%, and stability < 4.6% analyte loss after 30 days for b-VAMS, mean extraction yields > 74.0%, precision RSD < 5.6%, and stability < 4.9% analyte loss after 30 days for mfDBS. The original microsampling methodologies have been successfully applied to blood and plasma collected from psychiatric patients for the monitoring of the levels of clozapine and its metabolites, providing robust and reliable quali-quantitative results. Comparisons between results of the two dried microsampling technologies and with those obtained by classic fluid plasma analysis are in good agreement and have demonstrated that the proposed miniaturised approaches could be suitable for TDM purposes.